Innovative Design of Compact Heavy-Load Independent Transfer Device for Nuclear Engineering System - Hao Wan; Songfeng Weng; Hua Du; Dailin Dong; Bingyan Wang; Tianda Yu (Science and Technology of Nuclear Installations)
The transportation of heavy equipment in nuclear engineering has always been the focus of engineers, especially those transfer devices with the characteristics of small geometric size and heavy load. According to this kind of compact heavy-load transfer device and its engineering tasks, the core problems caused by excessive vertical and horizontal forces in the design process were analyzed. By introducing the theory of inventive problem solving (TRIZ) design method, these problems were creatively solved by the contradiction theory and substance-field model in TRIZ, and an innovative design scheme of the compact heavy load-independent transfer device was obtained. Through the analysis of the design scheme and the stability and rapidity of its hydraulic system, some key parameters were determined. The power of the transfer device was all from the hydraulic system, and it can carry up to 300 t weight of reactor equipment, while its geometric size was only 1600 × 400 × 500 mm. It was of great significance to improve the efficiency of the nuclear engineering system.